ANTIBACTERIAL EFFECT OF GNETUM GNEMON L. LEAVES EXTRACT ON STAPHYLOCOCCUS AUREUS - Dayoh, Paul J; Isbandiati, Endang; Rahayu, Titien (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction: Bacterial infections are common among doctors in Indonesia, leading toincreased use of antibiotics. Increased use of antibiotics, if not accompanied by rationalindication, can increase bacterial resistance. At present, alternative medicine from naturalingredients is widely studied, one of which is the leaves of melinjo (Gnetum gnemon L.).Melinjo leaves are thought to contain antibacterial compounds such as flavonoids, tannins,saponins, and alkaloids. Staphylococcus aureus is a round Gram-positive bacteria, that forms grape-like clusters. Staphylococcus aureus is a normal flora on the skin and human mucosa but can be opportunistic pathogens that cause mild to severe infections such as sepsis. Pathogenic Staphylococcus aureus can produce hemolysis blood, frozen plasma, and produce various extracellular enzymes and toxins. Purpose: This research aims to study the MIC and MBC of melinjo leaves extract on thegrowth of Staphylococcus aureus bacteria. This research is an experimental study with a posttest control group design. Method: Testing conducted using the microdilution method. Melinjo leaves used were extracted by maceration method using 96% ethanol. Samples were Staphylococcus aureus ATCC 25923 from BBLK Surabaya.Results: extract of melinjo leaves (Gnetum gnemon L.) had MIC on Staphylococcus aureus bacteria at a concentration of 640 mg/ml. MBC was not obtained because the extract of melinjo leaves clotted above 1280 mg/ml concentration. Conclusion: Melinjo leaves extract has an antibacterial effect against Staphylococcus aureus, the MIC is obtained at a concentration of 640 mg/ml, and the MBC cannot be determined.